Submerged injection of gas into a thin liquid sheet. (January 2019) - Li, Mingbo; Hu, Liang; Chen, Wenyu; Xie, Haibo; Fu, Xin
Highlights: Our study provides the first quantitative and qualitative overview of the events following submerged injection of gas into a thin quiescent liquid sheet with a thickness of a few millimeters. For the experimentally available range, three different flow regimes are identified and, particularly, we build a phase diagram outlining these regimes in terms of the Weber number and Bond number. We investigated the complete evolution of periodic bubbling-bursting behavior systematically. The bubbling characteristics, which show great differences with traditional bubbling in deep liquid, are depicted and analyzed. Using dimensional arguments, we proposed a scaling law for the rupture radius of bubbles which brings out the effects of gravity and inertia. Focusing on the subsequent liquid jet dynamics, we unravel experimentally the intricate roles of capillary wave velocities, cavity morphology, liquid thickness and gas momentum in bubble collapse. Our results and conclusions herein provide a new method for the control of the bursting-bubble jet and an important supplement to the physical problem of submerged gas injection. Abstract: Submerged injection of gas into a thin liquid sheet is frequently observed in industrial processes. Most studies on submerged gas injection, however, focus on the phenomena happened in deep liquid pool. Few studies have been devoted to a thin liquid layer with a thickness of a few millimeters. Here, we study submerged injection of gas into a thin liquid sheet, where we quantify the behaviors of bubbling/collapse and the resulting liquid jet with a high-speed video system. For the experimentally available range of liquid depths and gas velocities, three different flow regimes are identified and we build a phase diagram outlining these regimes in terms of the Weber number and Bond number. Particularly, the complete evolution of periodic bubbling-bursting behavior is investigated systematically. The bubbling characteristics, which show great differences with traditional bubbling in deep liquid, are depicted and analyzed. Using dimensional arguments, we propose a scaling law for the rupture radius of bubbles which brings out the effects of gravity and inertia. Focusing on the subsequent liquid jet dynamics, we unravel experimentally the intricate roles of capillary wave velocities, cavity morphology, liquid thickness and gas momentum in bubble collapse. With increase of the liquid sheet thickness, jets first become fat and small and then ends up thinner, detaching more and smaller droplets due to Rayleigh-Plateau instability. Our study firstly provides the quantitative overview of the events following submerged gas injection into thin quiescent liquid and provide guides for the control of the bursting-bubble jet.